45.9k views
1 vote
Let a, b, c and x elements in the group G. In each of the following solve for x in terms of a, b, and c.

Solve axb =c

1 Answer

3 votes

Answer:

The answer is
x=a^(-1)cb^(-1).

Explanation:

First, it is important to recall that the group law is not commutative in general, so we cannot assume it here. In order to solve the exercise we need to remember the axioms of group, specially the existence of the inverse element, i.e., for each element
g\in G there exist another element, denoted by
g^(-1) such that
gg^(-1)=e, where
e stands for the identity element of G.

So, given the equality
axb=c we make a left multiplication by
a^(-1) and we obtain:


a^(-1)axb =a^(-1)c.

But,
a^(-1)axb = exb = xb. Hence,
xb = a^(-1)c.

Now, in the equality
xb = a^(-1)c we make a right multiplication by
b^(-1), and we obtain


xbb^(-1) = a^(-1)cb^(-1).

Recall that
bb^(-1)=e and
xe=x. Therefore,


x=a^(-1)cb^(-1).

User Zeke
by
6.0k points